Communiqué of support of the Heads of State of UNASUR to the Government of the Republic of Paraguay regarding the establishment of the state of emergency, in some departments, due to the situation of insecurity affecting the country - Suramericanas, Unión de Naciones (2013)
Communiqué of Support of the Heads of States of the UNASUR to the Government of the Republic of Paraguay.